PECULIARITIES OF PEDAGOGICAL VISION FEOKTIST HARTAHAYEM THE PROCESS OF TEACHING LANGUAGES IN POLISH GYMNASIUMS OF THE SECOND HALF OF THE XIX CENTURY (Pedagogy of Higher and Secondary Education, 2007)
The language teaching methodology can be defined as the comparative methodology based on synthetic means taking into account perceptual psychology, teaching approach in native language, linguistic translating, mechanical and intentional reading.